The Role of Family Structure in Predicting Juvenile Delinquency - Bonnita Kemigisha (Uganda Christian University, 2025)
This study examined the correlation between family structure and juvenile delinquency, seeking to establish the type of family dynamics which mainly lead to delinquent behavior among minors. The case study was done at Naguru Remand Home in Kampala- Uganda focusing on juveniles below the age of 18 years. By evaluating different family setups, the study aimed at giving reliable insight on eradicating juvenile delinquency and improving intervention strategies. The Broken Home Theory, which links non-traditional family structures to higher delinquency rates, serves as a key framework for understanding these patterns. Data collection was done using qualitative methods, primarily interviews, allowing for a deeper exploration of participants' experiences. The findings will expand the body of knowledge and offer practical recommendations on eradicating juvenile delinquency and gender-based violence. These include implementing family education programs to raise awareness about the impact of different family structures and creating vocational training opportunities for at-risk youth to reduce delinquency. By addressing these factors, the study hopes to contribute to more effective solutions for juvenile rehabilitation and crime prevention.
Undergraduate